Vibrational and Quantum Chemical Study of Triphenylantimony(V)-o-salicylate - Tanveer Hasan; P. K. Singh; P. Raj; K. Singhal; Neeraj Misra (E-Journal of Chemistry)
A complete normal coordinate analysis was performed by two different methods: a classical Wilson G-F matrix method and the semi-empirical molecular orbital PM3 method, for a five coordinate non rigid triphenyl antimony diester SbPh3(O2CR)2,[R=C6H4OH-o], known to be a bioactive molecule. The study of vibrational spectra suggested that the title compound might have secondary bonding interaction between the central antimony atom and the carbonyl oxygen atoms. The atomic charge distribution, geometry optimization and thermochemistry, were also calculated by PM3 method, which help in finding the potential sites of the title compound.